1997
DOI: 10.1074/jbc.272.22.14037
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Inverts Protein Kinase A-mediated Regulation of Epithelial Sodium Channel Single Channel Kinetics

Abstract: Abnormal regulation of ion channels by members of the ABC transport protein superfamily has been implicated in hyperinsulinemic hypoglycemia and in excessive Na؉ absorption by airway epithelia in cystic fibrosis (CF). How ABC proteins regulate ion conductances is unknown, but must generally involve either the number or activity of specific ion channels. Here we report that the cystic fibrosis transmembrane conductance regulator (CFTR), which is defective in CF, reverses the regulation of the activity of single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
122
2
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 28 publications
9
122
2
3
Order By: Relevance
“…When NP o value was normalized to a value of 1 at Ϫ24 mV, the relative NP o was 2.54 Ϯ 0.68 (n ϭ 6) (p Ͻ 0.01) at Ϫ84 mV. Together, these results extend previous electrophysiological characterizations of rENaC stably expressed in 3T3 cells (10,11) and show that the biophysical properties of the macroscopic and microscopic currents attributable to the activity of rENaC expressed in these cells were similar to those observed in native Na ϩ -transporting epithelia, such as rat cortical collecting tubule (1) and other heterologous expression systems such as Xenopus oocytes and MDCK cells (3,16,30).…”
Section: Electrophysiological Properties Of Renac Heterologously Exprsupporting
confidence: 84%
See 1 more Smart Citation
“…When NP o value was normalized to a value of 1 at Ϫ24 mV, the relative NP o was 2.54 Ϯ 0.68 (n ϭ 6) (p Ͻ 0.01) at Ϫ84 mV. Together, these results extend previous electrophysiological characterizations of rENaC stably expressed in 3T3 cells (10,11) and show that the biophysical properties of the macroscopic and microscopic currents attributable to the activity of rENaC expressed in these cells were similar to those observed in native Na ϩ -transporting epithelia, such as rat cortical collecting tubule (1) and other heterologous expression systems such as Xenopus oocytes and MDCK cells (3,16,30).…”
Section: Electrophysiological Properties Of Renac Heterologously Exprsupporting
confidence: 84%
“…Cells-A previous study has shown that ␣␤␥rENaC-expressing 3T3 cells, but not untransfected 3T3 cells, exhibit an amiloride-sensitive conductance (10,11). By using the conventional whole-cell configuration with the standard cesium glutamate-rich pipette solution containing 2 mM ATP and lithium glutamate-rich bath solution, we first characterized in detail amiloride-sensitive macroscopic currents mediated by rENaC in this heterologous expression system.…”
Section: Electrophysiological Properties Of Renac Heterologously Exprmentioning
confidence: 99%
“…Functional expression of WT-CFTR, but not ⌬F508-CFTR, is associated with an inhibition of func- tional ENaC expression in oocytes (31). Such CFTR-mediated inhibition of ENaC is associated with a decrease in Na ϩ channel open probability, not with changes in levels of ENaC mRNA or protein expression (8,42,43). The forskolin/IBMX-regulated inhibition of ENaC by CFTR does not require expression of the full-length CFTR protein.…”
Section: Cftr Is a CLmentioning
confidence: 99%
“…The physiologic importance of the relationship between ENaC activity in airways and ASL volume is highlighted by two disease states, cystic fibrosis (CF) and pseudohypoaldosteronism type 1. In CF, the loss of functional cystic fibrosis transmembrane conductance regulator (CFTR) protein results in excessive ENaC activity (3,4), sodium hyperabsorption (5), and ASL volume depletion (6). The depletion of ASL volume, in turn, causes the overlying mucus gel to collapse onto cilia and the cell surface, thus disrupting mucociliary clearance (7).…”
mentioning
confidence: 99%
“…Similarly, while signals that raise intracellular cAMP in the kidney (e.g. vasopressin) increase ENaC currents by stimulating channel insertion into the plasma membrane (10,11), this second messenger pathway has little effect on amiloride-sensitive currents in normal airways (4). Finally, while patients with Liddle's syndrome manifest renal sodium hyperabsorption due to ENaC mutations (12)(13)(14), they do not appear to have sodium hyperabsorption across airway epithelia (15).…”
mentioning
confidence: 99%